2020
DOI: 10.1155/2020/2196024
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Membrane Progesterone Receptors in Eutopic and Ectopic Endometrium of Women with Endometriosis

Abstract: Endometriosis is one of the most frequent gynecological diseases in reproductive age women, but its etiology is not completely understood. Endometriosis is characterized by progesterone resistance, which has been explained in part by a decrease in the expression of the intracellular progesterone receptor in the ectopic endometrium. Progesterone action is also mediated by nongenomic mechanisms via membrane progesterone receptors (mPRs) that belong to the class II members of the progesterone and adipoQ receptor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
0
7
2
2
Order By: Relevance
“…In contrast to endometrial cancer [ 44 ] and endometriotic tissues [ 45 ] we did not observe decreased expression of progesterone membrane receptors in adenomyosis. Previous studies have shown that the mPRα and mPRβ expression at gene as well as protein levels was significantly downregulated in the ectopic endometrium of patients with endometriosis compared to the endometrium of healthy women [ 45 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to endometrial cancer [ 44 ] and endometriotic tissues [ 45 ] we did not observe decreased expression of progesterone membrane receptors in adenomyosis. Previous studies have shown that the mPRα and mPRβ expression at gene as well as protein levels was significantly downregulated in the ectopic endometrium of patients with endometriosis compared to the endometrium of healthy women [ 45 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to endometrial cancer [ 44 ] and endometriotic tissues [ 45 ] we did not observe decreased expression of progesterone membrane receptors in adenomyosis. Previous studies have shown that the mPRα and mPRβ expression at gene as well as protein levels was significantly downregulated in the ectopic endometrium of patients with endometriosis compared to the endometrium of healthy women [ 45 ]. We detected strong expression of mPRβ both in the stromal cells and the glandular epithelium, as well as mPRα and mPRγ, mainly in the cytoplasm of the glandular tissue, suggesting that adenomyosis is a separate disease, and may express molecular differences compared to endometriosis.…”
Section: Discussioncontrasting
confidence: 99%
“…mPRα and mPRβ were localized primarily to cell membranes, while mPRγ was localized in the cytoplasm and/or nucleus of normal endometrial tissue, while mPRα and mPRβ were detected at the cell membrane or in the cytoplasm, or both, while mPRγ was only localized in the cytoplasm of endometrial cancer tissue [ 37 ]. Within the context of endometriosis, mPRs expression was recently reported for both transcript and protein [ 38 ]. mPRα and mPRγ transcript expression ( PAQR7 and PAQR8 , respectively) were both lower in eutopic endometrium and ectopic lesion tissue compared to control endometrial tissue, while transcript expression of mPRβ ( PAQR8 ) and mPRδ ( PAQR6 ) was only reduced in the eutopic endometrium, with lesion tissue expressing similar levels to that of the control endometrium.…”
Section: Progesterone Receptors and Coactivators In Endometrial Physi...mentioning
confidence: 99%
“…Additionally, reduced PGRMC2, mPRα, mPRβ, and mPRγ expression has been observed in endometrial hyperplasia and endometriosis [ 11 , 162 , 163 ]. This finding confirms the role of PGRMC2 up-regulation in the secretory phase and how P4 acts through these receptors to inhibit cell proliferation.…”
Section: Pgr In the Uterusmentioning
confidence: 99%